1,5-Dichloro-4,8-dinitroanthraquinone - Armaghan, M.; Amini, M.M.; Ng, S.W. (International Union of Crystallography, 2010)
The ring skeleton of the title compound, C(14)H(4)Cl(2)N(2)O(6), is close to planar (r.m.s. deviation of the carbon atoms 0.091 A); the nitro goups are twisted with respect to the mean plane of the ring system by 70.8 (1) and 86.7 (2)degrees. The crystal studied was found to be a merohedral twin, with a domain ratio of 0.61 (8):0.39 (8).